Pemanfaatan Location Based Service Berbasis Android untuk Pemetaan Kantor Polisi Wilayah Kota Pekanbaru Riau - Gita Sastria; Fiza Febriyani; Dan Fatayat (Jurnal Penelitian Sains, 2017)
Police Station is one of institution community, has the function to serve the community as a community needs to police. The reality, a few people know where the location of the nearest police station in the city of Pekanbaru Riau and get information from every police station. It take a long time to get the right information, where is the right information about that police station. This study is applying geographic information system that provides information to the police station regarding to location, category of the police station and other information. This system was implemented using Location Based Service (LBS) on android mobile technology with Google Map is used to facilitate the search location, distance of the police station. This application was successfully mapping of police station in Pekanbaru Riau, its help community more easily to find the police station in accordance with wishes category information.